THE RURARL POPULATION OF UKRAINE IN PRESERVATION CULTURAL HERITAGE (1918 - 1991): REVION OF LITERATURE AND SOURCES AND FORMATION OF A DOCTORAL PROJECT AVENUE - Михайлюк, Віталій; Макаров, Максим (SWorldJournal, 2024)
The article deals with the method of development of a doctoral project on history. The purpose of the article provides for a review of published literature and sources, which is necessary to determine the preliminary plan of processing a doctoral project